16.8k views
2 votes
1/2 x + 3/4 y = -2 2/3 x + 5/6 y = -2 Solve the system.

User Ingdc
by
5.6k points

1 Answer

0 votes

Answer:

(2, -4)

Explanation:

1/2 x + 3/4 y = -2

2/3 x + 5/6 y = -2

4 (1/2 x + 3/4 y = -2 ) = -2(2x + 3y = -8) Multiply by -2 to eliminate the x's

6 (2/3 x + 5/6 y = -2) = (4x + 5y = -12)

-4x - 6y = 16 combine with the 2nd equation

-1y = 4

y = -4

plug -4 in for y to find x in either equation

1/2x + 3/4 (-4) =-2

1/2x - 3 = -2

1/2x = 1

x = 2

(2, -4)

User Mannekenpix
by
5.5k points